Study of Layout, Circulation, and Ornaments in Temple Building (Case Study: Satya Budhi Temple, Bandung) - Mustika Wardhani; Aldo Praseta; Salman Ramadhan; Thinka S Cahyowati; Debby N Achsanta (Itenas, Institut Teknologi Nasional Bandung, 2023)
The existence of temple buildings in Indonesia is part of the acculturation of Chinese culture that develops time by time. The temple, which is functionally used as a place of worship, has a unique role in historical developments in Indonesia, especially in Bandung. Satya Budhi Temple is one of the temple buildings in Bandung, which is more than 50 years old and is the oldest temple in this city. This building is part of the cultural heritage of Bandung, whose sustainability should be studied in terms of architecture. This research seeks to dig deeper into how the temple building's layout, circulation flow, and ornaments manifest the values of the Chinese philosophy of life, society, and culture. The research method uses a qualitative descriptive method accompanied by sketches of the elements forming space and circulation. The findings in this study show that the architecture of the temple has a distinctive spatial layout accompanied by a linear circulation which represents the journey towards the profane-sacred transition of humans towards God. From the findings of this study, it is hoped that cultural heritage buildings with a typology of worship places can continue to be preserved through preservation and revitalization efforts so that their historical value is well maintained.Keywords: Layout, Circulation flow, Ornament, Temple building, Cultural heritage building